Kepribadian Wirausaha Dan Strategi Kewirausahaan Sebagai Pendorong Keberhasilan Usaha Industri Makanan Khas Maluku - Fenri Abraham Stevi Tupamahu (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
This research is to examine the influence of entrepreneurial personality and entrepreneurial strategies on the success of the typical Maluku food industry. This type of research is an explanatory study; the analysis is carried out with the analysis approach using quantitative methods. The process of collecting data is done using a questionnaire instrument. The object of this research is a typical Maluku food industry unit operating in the Ambon Island Region, namely the Ambon City Administration Area and Central Maluku Regency. Total population of 167 units, the determination of the sample using probability sampling methods, sample selection in this study, using simple random sampling technique, the number of samples analyzed was 118 respondents. Quantitative data analysis methods use descriptive analysis methods and inferential statistical analysis techniques. Descriptive analysis uses mean, median and mode measurements. Inferential statistical analysis techniques using multiple regression methods. The results of the study explained the respondents' perceptions of entrepreneurial personality variables, entrepreneurial strategies and business success were relatively high. The results also prove that the entrepreneurial personality has a significant influence on the success of the typical Maluku food industry. The entrepreneurial strategy is proven to affect business success. Keywords: Entrepreneurial Personality, Strategic Entreprenenurship, Business Success